2021
DOI: 10.1186/s13293-021-00399-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific association of hair cortisol concentration with stress-related psychological factors in healthy young adults

Abstract: Background Hair cortisol concentration (HCC) has received attention as a useful marker of stress, but evidence on associations between psychological factors and cortisol concentration is inconsistent. The purpose of this study was to investigate the sex differences in the relationship between cortisol concentration and psychological factors in healthy young adults. Methods A total of 205 (103 females, 102 males) healthy young adults participated. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…No significant group differences were found in HCC. There was no significant difference in HCC regarding sex which confirms the findings in previous studies (Manenschijn et al, 2011 ; Raul et al, 2004 ; Thomson et al, 2010 ; Won Jae Kim et al, 2021a ). The CT+ group showed significantly higher scores of BDI and PSS than the CT– group.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…No significant group differences were found in HCC. There was no significant difference in HCC regarding sex which confirms the findings in previous studies (Manenschijn et al, 2011 ; Raul et al, 2004 ; Thomson et al, 2010 ; Won Jae Kim et al, 2021a ). The CT+ group showed significantly higher scores of BDI and PSS than the CT– group.…”
Section: Resultssupporting
confidence: 89%
“…Otherwise, considering the association between childhood adversity and a blunted cortisol response to social stress (Bunea et al, 2017 ), further studies investigating cortisol reactivity by acute stressors and basal cortisol levels might also reveal dysregulation of the cortisol response to chronic social stress in individuals with CT. Regarding the previous studies which reported no difference in HCC between sexes (Kim et al, 2021a ; Raul et al, 2004 ), we conducted univariable analysis to evaluate the relationship between sex and HCC. The univariable analysis showed that sex was associated with HCC at a trend level.…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous investigations have indicated that men had larger quantities of hair glucorticoids compared to women [ 21 , 22 , 47 , 56 , 57 , 58 ]. Nevertheless, several studies reported no significant differences in hair glucocorticoids between men and women [ 18 , 59 , 60 ]. Therefore, further research will be required to determine whether a gender differences in hair glucocorticoids exists and what mechanisms may be at work.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, literature has demonstrated the relevance of deregulation of the hypothalamic-pituitary-adrenal (HPA) axis in the presence of adipose tissue dysfunction as a contributing factor to accentuate the synthesis and secretion of cortisol, which consequently favors the increase of the risk for the development of metabolic disorders associated with obesity [6]. It is noteworthy that cortisol acts as an important regulator of endocrine function, metabolism, and adipocyte differentiation, contributing to adipogenesis and increased visceral fat stores [7]. Furthermore, this hormone is also involved in the central response to stress and indirectly in uences neuroprotection mechanisms [8].…”
Section: Introductionmentioning
confidence: 99%